The effectiveness of high-intensity interval training versus moderate intensity continuous training in prehabilitation among patients undergoing major abdominal surgery: A study protocol - Suriah Ahmad; Nor Azura Azmi; Nur Ayub Md Ali; Md Ali Katijjahbe; Ian Chik; Syarifah Noor Nazihah Sayed Masri; Adzim Poh Yuen Wen (PLoS ONE, 2025)
Background Prehabilitation programmes for major abdominal surgery enhance patients’ condition preoperative and promote recovery by building surgical resilience. However, the precise protocol of prehabilitation pertaining to the prescription of exercise training remains undefined. This paper describes the protocol of the study that aims to evaluate the effectiveness of high-intensity interval training (HIIT) compared to moderate intensity continuous training (MICT) among patients undergoing major abdominal surgery. Methods This is pragmatic double-blind randomized controlled trial, with parallel group, concealed allocation and blinding of patients and assessors. A total of 70 participants will be recruited from the surgery and anaesthetic clinic at the Hospital Canselor Tuanku Muhriz. Participants will be randomly allocated 1:1 to either receive HIIT (intervention group) or MICT (control group) with 35 participants in each group. Both groups will receive body conditioning and respiratory muscle strength exercises of HIIT for participants in the intervention group, while MICT for the control group. This will be one-hour therapist-supervised intervention sessions for at least 4 weeks duration with 1–3 sessions per week before the surgery. The patient will be assessed at baseline, before the operation at 4-week following intervention, prior to discharge, at 4 weeks and 3 months postoperatively. The primary outcome measures are 6-minute walking test and maximum inspiratory pressure. The secondary outcomes will be multidomain recovery of physical performances, psychological, and quality of life. All data will be analyzed using descriptive and inferential statistics, particularly Mixed Model ANOVA. The statistical significance value will be set at p < 0.05. The trial is currently recruiting participants. Conclusions The findings of this research will inform guidelines on optimal exercise dosage and intensity for prehabilitation in patients undergoing major abdominal surgery. Protocol registration The protocol of this study is registered in the Australia New Zealand Clinical Trial Registry with registration number ACTRN12625000023459.